2018
DOI: 10.1159/000487919
|View full text |Cite
|
Sign up to set email alerts
|

Membranous Nephropathy-Like Apolipoprotein E Deposition Disease with Apolipoprotein E Toyonaka (Ser197Cys) and a Homozygous Apolipoprotein E2/2

Abstract: A 20-year-old female student underwent renal biopsy because of chance proteinuria and hematuria. Histological study revealed a membranous nephropathy-like appearance by light microscopy. But immunoglobulins and complements were negative in the glomerulus by immunofluorescence study. On the other hand, plasma apolipoprotein E (ApoE) concentration was elevated to more than 2 times the normal range, and the phenotype, genotype, and DNA sequence studies of her ApoE showed homozygous ApoE2/2 and a heterozygous nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 18 publications
2
25
2
2
Order By: Relevance
“…Immunoglobulin and complement depositions were not specifically obsereved in immunofluorescence studies. Unlike the case reported by Fukunaga et al, 44 foam cells characteristic of apoE2 homozygote glomerulopathy and non-lamellated lipoprotein thrombi as reported by Sakatsume et al 20 were conspicuous in the cases reported by Hirashima et al 45 and Kato et al, 46 respectively. Therefore, in carriers exhibiting both apoE2 homozygote and apoE Toyonaka, the balance of non-immune MN-like lesions and apoE2 homozygote glomerulopathy may be dependent upon the influence of apoE Toyonaka within the hinge region.…”
Section: Apolipoprotein E (Apoe)mentioning
confidence: 57%
See 4 more Smart Citations
“…Immunoglobulin and complement depositions were not specifically obsereved in immunofluorescence studies. Unlike the case reported by Fukunaga et al, 44 foam cells characteristic of apoE2 homozygote glomerulopathy and non-lamellated lipoprotein thrombi as reported by Sakatsume et al 20 were conspicuous in the cases reported by Hirashima et al 45 and Kato et al, 46 respectively. Therefore, in carriers exhibiting both apoE2 homozygote and apoE Toyonaka, the balance of non-immune MN-like lesions and apoE2 homozygote glomerulopathy may be dependent upon the influence of apoE Toyonaka within the hinge region.…”
Section: Apolipoprotein E (Apoe)mentioning
confidence: 57%
“…[48][49][50] When apoE Toyonaka is involved in hinge damage, type III HLP induced by defective binding to the LDL receptor in the N-terminal domain of the apoE2 homozygote may be negated due to the dysfunction of the C-terminal domain that connects with lipids. In contrast, altered apoE without lipids may accumulate within the glomerulus and induce EDD in the subepithelial region, as the apoE molecule is relatively small (34 kDa) and rich in arginine, a positively-charged amino acid 4 The other 2 cases exhibiting apoE Toyonaka and apo E2 homozygosity 45,46 were of type III HLP with marked hypertriglyceridemia, which was different from the case presented by Fukunaga et al 44 The serum apoE levels, however, were high in all 3 cases. Spike formations were recognized by light microscopy, and subepithelial and subendothelial EDDs including microbubbles were both observed by electron microscopy.…”
Section: Apolipoprotein E (Apoe)mentioning
confidence: 61%
See 3 more Smart Citations